New media scholarship in Africa: an evaluation of Africa-focused blog related research from 2006 to 2016 - Elega, Adeola Abdulateef; Ozad, Bahire Efe (Springer, 2018)
This study reviewed Africa-focused blog related research during the 10-year period of 2006-2016 through a content analysis of 32 Africa-focused blog related research articles accessed from six databases: EBSCO's Academic Search Complete, Communication and Mass Media Complete, JSTOR, SAGE, Taylor and Francis, and Wiley Online Library. We evaluated Africa-focused blog related research areas, genres, trends, geospatial distribution, methods, and the journals that published these articles. Results show that majority of Africa-focused blog related research studied blogs, blog entries, and bloggers. Concerning blog genres, most of the articles focused on political blogs, activism, and news blogs. At least one article got published each year with a peak of seven in 2012. Most of the studies focused on South Africa, Egypt, and Kenya and, qualitative research methods were adopted more than quantitative research methods. The following journals; Communicatio, Ecquid Novi: African Journalism Studies, Journal of Communication Inquiry, and Journalism published more Africa-focused blog related research than others.
Keywords: Africa; Mass communication; New media; Blogs; Blogging research; Content analysis